The Psychological Effects of COVID-19 Pandemic in Patients with Inflammatory Bowel Disease - Eşkazan, Tuğçe; Bakkaloğlu, Oğuz Kağan; Durcan, Emre; Kurt, Enes Ali; Önal, Uğur; Candan, Selçuk; Tuncer, Murat; Demirel, Öznur; Hatemi, İbrahim and Erzin, Yusuf and et al. (Turkish Journal of Gastroenterology, 2022)
Background: Coronavirus disease 2019 pandemic was expected to have traumatic effects and increase the anxiety levels of inflamma- tory bowel disease patients. Methods: We aimed to investigate the psychosocial effects of the coronavirus disease 2019 pandemic on patients with inflammatory bowel disease by revealing the risk perception for present disease, coping strategies, follow-up characteristics, and treatment adher- ence. This is a cross-sectional, web-based survey study including 798 inflammatory bowel disease patients who were followed at our outpatient clinic and 303 volunteer who did not have any known chronic diseases and were not health professionals were included as the control group. Results: In this study, 281 of the patients were diagnosed with Crohn’s disease and 215 with ulcerative colitis. The mean age of patients with Crohn’s disease, ulcerative colitis, and the control group were 40.9 ± 13.1, 42.3 ± 12.7, and 39.9 ± 11.6, respectively. Here, 119 (42%) of the Crohn’s disease cases, 116 (54%) of the ulcerative colitis cases, and 170 (56%) of the control group were male. Among the 3 groups, coronavirus disease 2019-related post-traumatic stress disorder rates (Impact of Event Scale-Revised > 33) and State-Trait Anxiety Inventory of current status of anxiety-related anxiety rates were not statistically different while State-Trait Anxiety Inventory of anxiety tendency-related constant anxiety was higher in inflammatory bowel disease patients than the control group (P < .017). Conclusion: Inflammatory bowel disease patients with anxiety have a lower quality of life, and this may worsen the clinical course of the disease. Coronavirus disease 2019 is a major source of stress for such a vulnerable population. During the pandemic, psychological support and mental health awareness should be made accessible to all individuals.